Growth Effect of Balance of Payments and Monetary Policy in Nigeria (1980-2013): A Time Series Analysis (Global Journal of Management and Business Research, 2015)
Abstract not found
Keywords: balance of payments; monetary policy; economic growth; long-run; Nigeria